New Straits Times, 16 April 2003
Thirty-four men filed sexual abuse lawsuits totaling US$1.85 billion (RM7.03 billion) yesterday against the Roman Catholic diocese on New York's Long Island, claiming they were abused by priests and their complaints about that abuse ignored by church officials.